2015
DOI: 10.1103/physreva.91.042120
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity and trace-norm distances for quantifying coherence

Abstract: We investigate the coherence measures induced by fidelity and trace norm, based on the coherence quantification recently proposed by Baumgratz et al. [T. Baumgratz, M. Cramer, and M. B. Plenio, Phys. Rev. Lett. 113, 140401 (2014)]. We show that the fidelity of coherence does not in general satisfy the monotonicity requirement as a measure of coherence under the subselection of the measurement condition. We find that the trace norm of coherence can act as a measure of coherence for qubits and some special clas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
228
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(235 citation statements)
references
References 18 publications
6
228
0
Order By: Relevance
“…It is worth pointing out that the coherence measures induced by l 2 norm and the fidelity do not constitute valid coherence monotones, since for both quantities the strong monotonicity (2) does not hold in general [9,14]. Moreover, though the trace-norm measure of coherence was proved to be a strong monotone for all qubit and X states, a recent work showed that the trace norm of coherence cannot be regarded as a legitimate coherence measure for general states [15].…”
Section: Defining the Problemmentioning
confidence: 99%
“…It is worth pointing out that the coherence measures induced by l 2 norm and the fidelity do not constitute valid coherence monotones, since for both quantities the strong monotonicity (2) does not hold in general [9,14]. Moreover, though the trace-norm measure of coherence was proved to be a strong monotone for all qubit and X states, a recent work showed that the trace norm of coherence cannot be regarded as a legitimate coherence measure for general states [15].…”
Section: Defining the Problemmentioning
confidence: 99%
“…It has been shown that the promising fidelity of coherence does not in general satisfy (C2b) under the subselection of the measurement condition [9]. Generally, the bosonic single mode Hilbert space H is spanned by an uncountable basis {|n } ∞ n=0 called the Fock (number state) basis.…”
mentioning
confidence: 99%
“…Furthermore, a geometric measure of coherence is also proposed [15,18,19] which is a full coherence monotone [18]. The geometric measure is given by C g (ρ) = 1 − max σ∈I F(ρ, σ), where I is the set of all incoherent states and…”
Section: A Quantum Coherencementioning
confidence: 99%
“…Moreover, combined with the tensor product structure of quantum state space, it gives rise to the novel concepts such as entanglement and quantum correlations. It, being the premise of quantum correlations in multipartite systems, has attracted the attention of quantum information community significantly, and * asukumar@hri.res.in in addition to its quantification [17][18][19], other developments like the freezing phenomena [20], the coherence transformations under incoherent operations [21], establishment of geometric lower bound for a coherence measure [22], the complementarity between coherence and mixedness [23], its relation with other measures of quantum correlations and creation of coherence using unitary operations [24,25], erasure of quantum coherence [26], and catalytic transformations of coherence [27] have been reported recently.…”
Section: Introductionmentioning
confidence: 99%